Effect of Parenchymal Stiffness on Canine Airway Size with Lung Inflation - Brown, Robert H. (Public Library of Science, 2010)
Although airway patency is partially maintained by parenchymal tethering, this structural support is often ignored in many discussions of asthma. However, agonists that induce smooth muscle contraction also stiffen the parenchyma, so such parenchymal stiffening may serve as a defense mechanism to prevent airway narrowing or closure. To quantify this effect, specifically how changes in parenchymal stiffness alter airway size at different levels of lung inflation, in the present study, we devised a method to separate the effect of parenchymal stiffening from that of direct airway narrowing. Six anesthetized dogs were studied under four conditions: baseline, after whole lung aerosol histamine challenge, after local airway histamine challenge, and after complete relaxation of the airways. In each of these conditions, we used High resolution Computed Tomography to measure airway size and lung volume at five different airway pressures (0, 12, 25, 32, and 45 cm H(2)O). Parenchymal stiffening had a protective effect on airway narrowing, a fact that may be important in the airway response to deep inspiration in asthma. When the parenchyma was stiffened by whole lung aerosol histamine challenge, at every lung volume above FRC, the airways were larger than when they were directly challenged with histamine to the same initial constriction. These results show for the first time that a stiff parenchyma per se minimizes the airway narrowing that occurs with histamine challenge at any lung volume. Thus in clinical asthma, it is not simply increased airway smooth muscle contraction, but perhaps a lack of homogeneous parenchymal stiffening that contributes to the symptomatic airway hyperresponsiveness.